2011
DOI: 10.1038/embor.2011.52
|View full text |Cite
|
Sign up to set email alerts
|

Lgr4 is required for Paneth cell differentiation and maintenance of intestinal stem cells ex vivo

Abstract: Gene inactivation of the orphan G protein-coupled receptorLGR4, a paralogue of the epithelial-stem-cell marker LGR5, results in a 50% decrease in epithelial cell proliferation and an 80% reduction in terminal differentiation of Paneth cells in postnatal mouse intestinal crypts. When cultured ex vivo, LGR4-deficient crypts or progenitors, but not LGR5-deficient progenitors, die rapidly with marked downregulation of stem-cell markers and Wnt target genes, including Lgr5. Partial rescue of this phenotype is achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(131 citation statements)
references
References 30 publications
8
121
1
1
Order By: Relevance
“…4A). By using an unambiguous Paneth cell marker, we observed that the number of Paneth cells was 80 -85% lower in Lgr4 mutant mice when compared with WT mice, which is consistent with a previous study (27) (Fig. 4, B and C).…”
Section: Impaired Proliferation But Not Apoptosis Of Intestinal Cryptsupporting
confidence: 92%
See 3 more Smart Citations
“…4A). By using an unambiguous Paneth cell marker, we observed that the number of Paneth cells was 80 -85% lower in Lgr4 mutant mice when compared with WT mice, which is consistent with a previous study (27) (Fig. 4, B and C).…”
Section: Impaired Proliferation But Not Apoptosis Of Intestinal Cryptsupporting
confidence: 92%
“…Because the Lgr4 mutant mouse model is different from the Paneth cell depletion models, we speculate that Lgr4 could regulate Bmi1 ϩ stem cell numbers, which was supported by Mustata et al (27), who demonstrated that the Bmi1 mRNA level was decreased in Lgr4 mutant crypts. Moreover, Yan et al (36) reported that Lgr5 ϩ ISCs were dependent on R-spondin1, which is also essential for in vitro culture of Bmi1 ϩ ISCs.…”
Section: E and F Lgr4mentioning
confidence: 65%
See 2 more Smart Citations
“…However, because the Wnt pathway drives the expression of several target genes in ISCs [20], the lack of expression of some targets is not equivalent to the lack of Wnt signaling. For example, Lgr5, the first Wnt target gene found to definitively mark the crypt base stem cells, is not required for stem cell maintenance [24,32]. Thus, the lack of expression of Lgr5 in tumor 'Lgr5 cell' signatures is unlikely to impact the stemness of those cells.…”
Section: Gene Expression Signatures Of Intestinal Stem Cells Bulk Up mentioning
confidence: 99%